(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
Sedimentary rocks are our window to understand the history and evolution of the surface of our planet. The sedimentary record, although biased by variable preservation conditions and post depositional processes, potentially preserve signals of the interaction between physical, chemical and biological processes that takes place at the interface between the Geosphere, the Hydrosphere/ Atmosphere and the Lithosphere. Geochemistry, integrated with Sedimentology, has become a standard approach to unravel these interactions and to provide some insights for the understanding of how sedimentary geochemistry is preserved within different sedimentary environments. Microbial life is ubiquitous at the Earth’s surface (Whitman et al., 1998), and has been present throughout our Planet’s history. It has evolved to exploit the energy provided by gradients in geochemical composition between rocks, organic materials and surface fluids, using this energy for maintenance and growth (Hoeler, 2007). Due to their abundance, chemical reactivity and metabolic activity (Konhauser, 2007), microbes play a central role in biogeochemical cycles (C, O, N, S, Fe, etc) at both, micro and macroscopic scales (Schlesinger and Bernhardt, 2020). The best example of these processes are the current chemical composition of our O2-rich atmosphere or the chemical redox gradients that exist at the sediment-water interface in most sedimentary environments around the world, where early diagenesis driven by organic matter degradation takes place (Aller, 2014). In addition, microbial mats and biofilms influence the precipitation/dissolution of minerals such as carbonates (explaining the the abundance of microbialites in the ancient rock record, Riding, 2011) as well as the rheological and mechanical behaviour of detrital sediments, where a classic example are known as MISS (Microbially induced sedimentary structures, Noffke et al., 2010). For these reasons, whenever we talk about sedimentary geochemistry we are actually talking about sedimentary biogeochemistry and geomicrobiology. This is so since microbial activity has been shaping the surface chemistry and composition of our planet, as previously recognized by the pioneering work of Vladimir Vernadsky in 1926 and later by Lourens Baas-Becking in 1934 (Knoll et al., 2012). Vernadsky and Baas-Becking early ideas have grown and become the lens through which we scientifically observe our world, making it clear that the Biosphere adds another layer of diversity and complexity in order to understand our planet as a system.